Clinical course of 2019 novel coronavirus disease (COVID-19) in individuals present during the outbreak on the Diamond Princess cruise ship. Issue 8 (August 2020) - Kato, Hideaki; Shimizu, Hiroyuki; Shibue, Yasushi; Hosoda, Tomohiro; Iwabuchi, Keisuke; Nagamine, Kotaro; Saito, Hiroki; Sawada, Reimin; Oishi, Takayuki; Tsukiji, Jun; Fujita, Hiroyuki; Furuya, Ryosuke; et al.
Abstract: We investigated the clinical course of individuals with 2019 novel coronavirus disease (COVID-19) who were transferred from the Diamond Princess cruise ship to 12 local hospitals. The conditions and clinical courses of patients with pneumonia were compared with those of patients without pneumonia. Among 70 patients (median age: 67 years) analyzed, the major symptoms were fever (64.3%), cough (54.3%), and general fatigue (24.3%). Forty-three patients (61.4%) had pneumonia. Higher body temperature, heart rate, and respiratory rate as well as higher of lactate dehydrogenase (LDH), aspartate aminotransferase (AST), and C-reactive protein (CRP) levels and lower serum albumin level and lymphocyte count were associated with the presence of pneumonia. Ground-glass opacity was found in 97.7% of the patients with pneumonia. Patients were administered neuraminidase inhibitors (20%), lopinavir/ritonavir (32.9%), and ciclesonide inhalation (11.4%). Mechanical ventilation and veno-venous extracorporeal membrane oxygenation was performed on 14 (20%) and 2 (2.9%) patients, respectively; two patients died. The median duration of intubation was 12 days. The patients with COVID-19 transferred to local hospitals during the outbreak had severe conditions and needed close monitoring. The severity of COVID-19 depends on the presence of pneumonia. High serum LDH, AST and CRP levels and low serum albumin level and lymphocyte count were found to be predictors of pneumonia. It was challenging for local hospitals to admit and treat these patients during the outbreak of COVID-19. Assessment of severity was crucial to manage a large number of patients.